PENGARUH LINGKUNGAN KERJA, DISIPLIN DAN TUNJANGAN PROFESI GURU TERHADAP KINERJA GURU MADRASAH ALIYAH NEGERI 3 TAPANULI SELATAN - Syahbari Efendi; Purnomo Setyo Prakoso; Sarima Pulungan; Sri Rahmadani; Siti Ummi Arfah Nasution (Universitas Islam Islam Sumatera Utara, 2020)
The purpose of this research was to determine and analyze the influence of Work Environment, Discipline and Teacher Professional Allowance on the Performance of Teachers in Madrasah Aliyah Negeri 3 Tapanuli Selatan, both partially and simultaneously. The sample in this research were all employees, amounting to 35 teachers. Determination of the number of samples using a saturated sample (census). The analysis technique used is descriptive analysis method and multiple linear regression analysis with SPSS 20.00 for windows. The results showed that :1) Work environment had a positive and significant effect on the performance of teachers in Madrasah Aliyah Negeri 3 Tapanuli Selatan; 2) Discipline has a positive and significant effect on the performance of teachers in Madrasah Aliyah Negeri 3 Tapanuli Selatan; 3) Teacher professional allowance has a positive and significant effect on the performance of teachers in Madrasah Aliyah Negeri 3 Tapanuli Selatan; 4) Work environment, discipline and teachers professional allowance has a positive and significant effect on the performance of teachers in Madrasah Aliyah Negeri 3 Tapanuli Selatan. Work environment, discipline and teacher professional allowance have the ability to explain its effect on the performance of teachers variable of Madrasah Aliyah Negeri 3 Tapanuli Selatan at 59.0%, while the remaining 41.0% is the influence of other independent variables not examined in this research.